2018
DOI: 10.1002/jid.3352
|View full text |Cite
|
Sign up to set email alerts
|

Tax Revenue Mobilization in Conflict‐affected Developing Countries

Abstract: How does conflict affect tax revenue mobilization? This paper uses a newly updated dataset to explore longitudinal trends of tax revenue mobilization prior to, during and after conflict periods in a selection of conflict-affected states since 1980. This medium-N trend analysis provides greater insight into the relationship between tax revenue performance over time and the characteristics of the conflicts in question. Offering detailed snapshots of tax experiences prior to, during and after conflict, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For the single-variable Models 1a and 2a, the results show that holding other macroeconomic and institutional factors constant, the coefficient of armed conflict intensity yields a negative and significant sign in the tax revenue equation but a positive and significant sign in the mineral rents equation. It thus appears that, for tax revenue, the Eurocentric view that an escalation of armed conflicts could fuel the government's efforts to raise additional revenue (Van Den Boogaard et al, 2018) might not be true under idealized stable macroeconomic and institutional conditions. In the mineral rents equation, that the coefficient of armed conflict intensity turns positive and significant is an indication that under a constant macroeconomic condition, the 'relative deprivation' principle holds, especially as mineral resource exploitation becomes a basis for economic competition between government and insurgent groups.…”
Section: Impact Of Armed Conflict Intensity On Revenue and Expenditur...mentioning
confidence: 99%
See 2 more Smart Citations
“…For the single-variable Models 1a and 2a, the results show that holding other macroeconomic and institutional factors constant, the coefficient of armed conflict intensity yields a negative and significant sign in the tax revenue equation but a positive and significant sign in the mineral rents equation. It thus appears that, for tax revenue, the Eurocentric view that an escalation of armed conflicts could fuel the government's efforts to raise additional revenue (Van Den Boogaard et al, 2018) might not be true under idealized stable macroeconomic and institutional conditions. In the mineral rents equation, that the coefficient of armed conflict intensity turns positive and significant is an indication that under a constant macroeconomic condition, the 'relative deprivation' principle holds, especially as mineral resource exploitation becomes a basis for economic competition between government and insurgent groups.…”
Section: Impact Of Armed Conflict Intensity On Revenue and Expenditur...mentioning
confidence: 99%
“…On the other hand, there is the Eurocentric school that says that the escalation of armed conflicts or wars can lead to an increase in public revenue mobilization and consolidation of state formation efforts (Van Den Boogaard et al, 2018). The argument here is that states facing a threat of attack would have more incentives to raise tax revenues to meet the security challenges and that the willingness to pay tax on the part of the citizens is often greater during such a time (Ertman, 1997).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Parfenova et al (2016) have indicated that the impact of the tax policy of the state is vital for a country's economy. Further, the core importance of taxes to wider development objectives shows that strengthening tax systems should be a central issue in strategies for state building, especially in post-conflict circumstances (van den Boogaard et al 2018). When it comes to economic implications, tax reduction policies can enhance economic development, employment, and social equity (Liu and Zhang 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FS face structural challenges in expanding and sustaining tax revenue as a percentage of GDP, and their tax administration structures are generally weaker. 3 The destruction of infrastructure, the disruption of the administrative and bureaucratic capacity, and the slowdown of economic activity following long periods of political instability narrow the tax revenue base and undermine fiscal discipline (Van den Boogaard et al, 2018;Addison and Murshed, 2001). Long periods of political unrest -in the sense of continuity of regime and institutions -also hinder fiscal reform processes and may interrupt technical assistance projects by development partners (Chowdury and Murshed, 2016).…”
Section: Introductionmentioning
confidence: 99%